2016
DOI: 10.1155/2016/4569742
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study to Examine Perceptions and Barriers to Appropriate Gestational Weight Gain among Participants in the Special Supplemental Nutrition Program for Women Infants and Children Program

Abstract: Women of reproductive age are particularly at risk of obesity because of excessive gestational weight gain (GWG) and postpartum weight retention, resulting in poor health outcomes for both mothers and infants. The purpose of this qualitative study was to examine perceptions and barriers to GWG among low-income women in the WIC program to inform the development of an intervention study. Eleven focus groups were conducted and stratified by ethnicity, and each group included women of varying age, parity, and prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The determinants in women of childbearing age as found in this study, were comparable to determinants of lifestyle behavior in the general population as found in previous studies [9,16,19,[35][36][37][38]. The findings of period specific determinants are especially relevant when supporting women to adopt a healthy lifestyle continuously in the periods before, during and after pregnancy.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The determinants in women of childbearing age as found in this study, were comparable to determinants of lifestyle behavior in the general population as found in previous studies [9,16,19,[35][36][37][38]. The findings of period specific determinants are especially relevant when supporting women to adopt a healthy lifestyle continuously in the periods before, during and after pregnancy.…”
Section: Discussionsupporting
confidence: 87%
“…[35][36][37][38][39] years of age; parity 1; preconception): "Once I have read that when you are overweight, that becoming pregnant could take a longer time […] I would like to prevent that." Participant 18 (20-24 years of age; parity 1; postpartum and preconception): "Actually I only want to become pregnant when my weight is adequate.…”
mentioning
confidence: 99%
“…The intervention was designed to help WIC participants avoid gaining weight beyond the IOM recommendations for GWG. Based on extensive qualitative research in which the study team conducted focus groups with pregnant WIC participants (Kim, Koleilat, & Whaley, 2016), the intervention was designed with two major components that could be easily integrated into core WIC services: guidance about monitoring GWG using a pregnancy weight tracker (GWG Tracker) adapted from the IOM (The Institute of Medicine [IOM] & National Research Council of the National Academies, n.d.) and accompanying three oneon-one education sessions with a WIC nutritionist.…”
Section: Interventionmentioning
confidence: 99%
“…Because weight gain recommendations are not the same for all women, but vary based on their pre-pregnancy weight, dissemination of appropriate materials can be challenging in a busy public health clinic setting. In addition, feedback from focus groups strongly suggested that women prefer information tailored to their specific needs and not generic information that may or may not apply to them (Kim, Koleilat, & Whaley, 2016). To facilitate ease of use as well as personalization of the tracker, we created trafficlight color-coded trackers for each of the four pre-pregnancy BMI groups: green for normal weight women, yellow for overweight women, red for obese women and blue for underweight women.…”
Section: Gwg Monitoring Component Using the Gwg Trackermentioning
confidence: 99%
See 1 more Smart Citation